La lúdica para facilitar el proceso de adaptación en niños de 2 a 3 años del centro de desarrollo infantil Clodoveo de la ciudad de Loja, en el periodo 2019-2020. - Vargas Sarango, Cindy María (2021)
The adaptation period in children's centers is a stage of changes in the lives of children onan emotional, cognitive and social level; therefore, the present research work has as generalobjective: to identify if ludic facilitates the adaptation process in children from 2 to 3 yearsold; the following methods were used: descriptive, scientific, analyticalsynthetic and comparative, which allowed structuring, explaining, describing and tabulating the results of the research; The techniques and instruments for the data collection were: the survey applied to 2 educators from the center which served as a guide to identify the problem to be researched, in the same way the adaptation assessment sheet was applied to 19 childrenfrom 2 to 3 years old, in order to identify the causes why children were at a low level of adaptation; being this the studied population. Thanks to the initial diagnostic, it was foundthat 60% of the researched population presented inappropriate behaviors; maladaptive conducts and a low level of oral expression, in order to favor adaptation, the didactic guidecalled "little by little I explore" was applied based on ludic activities, which contributed tominimize 88% of these inappropriate behaviors and maladaptive conducts; in the same way, the verbal and gestural expression improved significantly. For this reason, it is recommended to incorporate these activities to school planning in order to use ludic activities to establish a warm and friendly atmosphere among children; since this allows them to participate in the environment that surrounds them and achieve a healthy coexistence which will help to achieve a correct adaptation.